Characterization of the passive and active material parameters of the pubovisceralis muscle using an inverse numerical method. (11th April 2018) - Silva, M.E.T.; Parente, M.P.L.; Brandão, S.; Mascarenhas, T.; Natal Jorge, R.M.
Abstract: The mechanical characteristics of the female pelvic floor are relevant to understand pelvic floor dysfunctions (PFD), and how they are related with changes in their biomechanical behavior. Urinary incontinence (UI) and pelvic organ prolapse (POP) are the most common pathologies, which can be associated with changes in the mechanical properties of the supportive structures in the female pelvic cavity. PFD have been studied through different methods, from experimental tensile tests using tissues from fresh female cadavers or tissues collected at the time of a transvaginal hysterectomy procedure, or by applying imaging techniques. In this work, an inverse finite element analysis (FEA) was applied to understand the passive and active behavior of the pubovisceralis muscle (PVM) during Valsalva maneuver and muscle active contraction, respectively. Individual numerical models of women without pathology, with stress UI (SUI) and POP were built based on magnetic resonance images, including the PVM and surrounding structures. The passive and active material parameters obtained for a transversely isotropic hyperelastic constitutive model were estimated for the three groups. The values for the material constants were significantly higher for the women with POP when compared with the other two groups. The PVM of women with POP showed the highest stiffness. Additionally, the influence of these parameters was analyzed by evaluating their stress-strain, and force-displacements responses. The force produced by the PVM in women with POP was 47% and 82% higher when compared to women without pathology and with SUI, respectively. The inverse FEA allowed estimating the material parameters of the PVM using input information acquired non-invasively.